2018
DOI: 10.1016/j.jim.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Precision-cut human liver slice cultures as an immunological platform

Abstract: The liver is the central metabolic organ in the human body, and also plays an essential role in innate and adaptive immunity. While mouse models offer significant insights into immune-inflammatory liver disease, human immunology differs in important respects. It is not easy to address those differences experimentally. Therefore, to improve the understanding of human liver immunobiology and pathology, we have established precision-cut human liver slices to study innate immunity in human tissue. Human liver slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 49 publications
5
95
0
Order By: Relevance
“…Previous studies have cultured PCLS directly on plastic, where their longevity and functionality either is severely limited (to <48h) or prolonged PCLS longevity to up to 72h by culturing in high oxygen concentrations with or without gentle shaking in a circular motion[24, 25]. Whilst most culture systems use fully submerged PCLS, a recent study described a rocked platform where hPCLS are cultured on organoid transwell plates in an air-liquid interface in normoxia for up to 15 days[14]. The air-liquid interface system cultures PCLS that are exposed to air on the upper side and are submerged in media on the lower side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have cultured PCLS directly on plastic, where their longevity and functionality either is severely limited (to <48h) or prolonged PCLS longevity to up to 72h by culturing in high oxygen concentrations with or without gentle shaking in a circular motion[24, 25]. Whilst most culture systems use fully submerged PCLS, a recent study described a rocked platform where hPCLS are cultured on organoid transwell plates in an air-liquid interface in normoxia for up to 15 days[14]. The air-liquid interface system cultures PCLS that are exposed to air on the upper side and are submerged in media on the lower side.…”
Section: Discussionmentioning
confidence: 99%
“…The air-liquid interface system cultures PCLS that are exposed to air on the upper side and are submerged in media on the lower side. This alternative system was used to evaluate the immunological responses to viral and bacterial products in PCLS at a gene expression level [14] but of note the authors reported substantial fibrogenesis which prevented the model from being used to study induced fibrosis. By contrast our bioreactor was specifically designed to minimise hepatocellular damage to limit background fibrogenesis and thereby enable investigations of induced fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these have also proven valuable for the identification of new therapeutic targets, as recently demonstrated for influenza A-associated pneumococci co-infections [67], and the testing of preventive interventions, as exemplified by certain vaccines [68]. Similarly, human liver slices (hLS) have proven valuable to the study of viral life cycles, the assessment of antiviral drugs efficacy [69], and monitoring of local innate immune responses [70]. An elegant study [71] tested 8 approved drugs with known liver-related effects in hLS by assessing relevant markers of oxidative stress, mitochondrial function, and drug metabolism.…”
Section: Current Applications Of Human-based Test Models In Pharmacolmentioning
confidence: 99%
“…Strategies to minimize the detrimental effects of hypoxia in PCLSs and limit accumulation of metabolites include: increasing oxygen concentration from 20% to 40%‐95%, using synthetic oxygen carriers (e.g., perfluorodecalin; varying media supplements/composition or introducing media flow by rocking or shaking the PCLS, using rotating culture vessels/rollers or perfusion circuits . Recently, an air‐liquid interface culture system has been used to model inflammation and immunological processes in human PCLSs over a 15‐day culture period, although of note this methodology was associated with significant spontaneous fibrogenesis and apoptosis . A significant advantage of PCLSs over animal models is that PCLSs can be generated from human liver; therefore, liver disease biology, efficacy of therapies, and drug metabolism can be modeled in human tissue ex vivo …”
mentioning
confidence: 99%